Журнал "Рідна церква" (1952–1988) як джерело до вивчення УАПЦ в діаспорі (до 70-річчя від дня заснування) - Фульмес, В. (Краєзнавство, 2022)
Вивчаючи повсякденне життя, діяльність та служіння Української Церкви поза межами України доцільним є звернення до тогочасних періодичних видань як важливих джерел та цінної хроніки з історії церкви й української діаспори. На шпальтах цих видань репрезентувалася активна діяльність і життя Церкви закордоном. У статті розглянуто історію заснування та здійснено огляд українського православного церковно-релігійного журналу «Рідна Церква», що виходив у 1952– 1988 рр. в Німеччині. Встановлено його значення як цінного джерела та хроніки до вивчення УАПЦ і дослідження церковно-релігійного життя української спільноти в діаспорі. Today, the study and research of the Ukrainian Church outside the borders of Ukraine, its daily service and activities arouse considerable interest among scientists. An important mission of the Church of Christ is to cover all areas of society, including the information space. Therefore, the Church in diaspora could not do without its mass media. It is appropriate to turn to periodicals of that time as important sources and valuable chronicles of the history of the church and the Ukrainian diaspora, whose columns represented the active activity and life of the church abroad. This year marks the 70th anniversary of the founding of the Ukrainian Orthodox church and religious journal «Native Church» – the printed organ of the UAOC, which was published in Germany in 1952-1988. The founder and editor of this journal was Metropolitan of Paris and Western Europe Anatoly (Dublyansky) (1912–1997). He etched his name in Ukrainian culture as a local historian, museum worker and editor of local newspapers, and during the war years and in the post-war emigration period of his life, he was an active member of the UOAC, worked as a parish priest, editor of the printed organ of the UAOC, a church administrator, and later – bishop of the UOAC, holding a chair in Western Europe. Father Anatolii Dublyansky, already at the initial stage of church activity, showed himself as a zealous executor of the duties assigned to him not only as a priest. The editorial experience came in handy for the establishment of the printed edition of the UOAC – the Ukrainian Orthodox church and religious jouranl «Native Church», which played a major role in the activities of the Church in emigration. The purpose of this jouranl was to spread the ideas of Orthodoxy and to inform about the UAOC. The readership consisted not only of Ukrainians in Germany, but also of the entire diaspora, as well as foreigners who were interested in the fate of the UAOC. The journal’s high degree of informativeness makes it a valuable source for researching the activities of the UOAC in diaspora and certain church figures. The article examines the history of the push and reviews the Ukrainian Orthodox church and religious journal «Native Church», which was published in Germany in 1952–1988. Its significance as a valuable source and chronicle for the study of the UOAC and the study of the church and religious life of the Ukrainian community in the diaspora has been established.